AN ANALYSIS OF DEIXIS IN JOHN CLAYTON MAYER’S YOU ARE GONNA LIVE FOREVER IN ME SONG - Dina Nur'Aini Zahra; Nai Supartini Atmawidjaja (IKIP Siliwangi, 2024)
Language is more than a tool used to communicate between humans, but also becomes an inseparable part that makes language have various meanings and can be enjoyed by humans. One of the fields that humans can learn from language is pragmatics, which has a sub-study of deixis. Deixis is a sub-study of pragmatics that studies how to study a word related to name, place, time, position, etc. Deixis is found in many media around humans, one of which is music as an entertainment medium. In this study, the author is interested in conducting a deixis analysis of the song with the title